Deep trap sites suppressing space charge injection in polycyclic aromatic compounds doped XLPE composite. Issue 1 (12th February 2020) - Li, Jin; Han, Chenlei; Du, Boxue; Takada, Tatsuo
Abstract : In this study, the space charge characteristics in the polycyclic aromatic compounds doped cross‐linked polyethylene (XLPE) composite were analysed by integration current ( Q ( t )) method and quantum chemical calculation. Experimentally, the space charge behaviours of XLPE composites modified by the three selected polycyclic aromatic compounds during polarisation and depolarisation process at 25 and 80°C were measured by Q ( t ) method, respectively. The energy levels and 3D potential distributions of the three polycyclic aromatic compounds were calculated by density functional theory. The experimental and calculation results indicate that the polycyclic aromatic compound C with deep carrier traps and stronger polarity exhibits outstanding ability to reduce space charge injection than the others at both 25 and 80°C. Generally, 4, 4′‐bis (dimethyl amino) benyil has great potential as the organic additive for DC cable insulation from the view of space charge suppression.